2015
DOI: 10.1073/pnas.1519807112
|View full text |Cite
|
Sign up to set email alerts
|

Shifting eating to the circadian rest phase misaligns the peripheral clocks with the master SCN clock and leads to a metabolic syndrome

Abstract: The light-entrained master central circadian clock (CC) located in the suprachiasmatic nucleus (SCN) not only controls the diurnal alternance of the active phase (the light period of the human lightdark cycle, but the mouse dark period) and the rest phase (the human dark period, but the mouse light period), but also synchronizes the ubiquitous peripheral CCs (PCCs) with these phases to maintain homeostasis. We recently elucidated in mice the molecular signals through which metabolic alterations induced on an u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
137
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 161 publications
(150 citation statements)
references
References 40 publications
11
137
0
2
Order By: Relevance
“…Actually, a recent paper has shown that a long term of RF induces diabetes, fatty liver and obesity in mice42. Thus, our results provide a new clue to understand the link between perturbation of the circadian rhythm system and the development of metabolic syndrome.…”
Section: Discussionsupporting
confidence: 52%
“…Actually, a recent paper has shown that a long term of RF induces diabetes, fatty liver and obesity in mice42. Thus, our results provide a new clue to understand the link between perturbation of the circadian rhythm system and the development of metabolic syndrome.…”
Section: Discussionsupporting
confidence: 52%
“…The results of the current study confirmed the existence of a peripheral clock in silkworm BmN cells44. Recent studies have shown that changes in feeding patterns may disrupt the peripheral clock in mice, leading to metabolic syndrome4546, while a fat-metabolism disorder in Drosophila caused by food restriction was also regulated by the peripheral clock47. However, although individual animal cells have spontaneous rhythms, they are also regulated by the core cranial nerve core.…”
Section: Discussionsupporting
confidence: 85%
“…As RF early metabolic alterations did affect the expression of Per1, Per2, and RevErbα, we analyzed the transcript of CC components after RF for 4, 8, 15, 30, and 90 d. In liver and IECs, all of them were shifted after RF4, but it took 8 d to achieve the same shifts in muscle and heart (see below). Importantly, once established these shifts were stable as long as RF was not interrupted, whereas the "original circadian active and rest phases" remained unchanged throughout the RF period (13).…”
Section: Glucose Administration Prevents Metabolic and Pcc Alterationsmentioning
confidence: 96%